Indonesian Language Learning through Digital Media among Children in Kerembong Village (Lombok) - Putra, Agus Darma; Fikri, Muhammad; Muhammad, Syahdan (Journal of Education and Social Science, 2024)
Learning through digital media is a current trend. This is no exception with the Indonesian language learning carried out by the children in the village of Change. They learn Indonesian through digital media according to the model or method directed by their tutor. The purpose of writing this article is to explain: (1) the Indonesian language learning model using digital media among children in the village of Change; (2) the positive and negative impacts of learning Indonesian using digital media on children in the village of Change. The approach used is a qualitative approach with a descriptive method. Meanwhile, what is at the core of the discussion in this article is the Indonesian language learning model using digital media such as google and youtube among children in the village of Change, and the positive and negative impacts of learning Indonesian using digital media.